Processos de gestão da informação: tratamento, recuperação e uso da informação no mercado de capitais - Lopes, Elaine Cristina [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (My University, 2013)
In the capital market the information are used as subsidies for the decision making of investors, among the main highlights are the economic, political, accounting and relating nature to the financial results of companies which have stocks traded at Stock Exchanges. In this perspective, it is essential that the agents involved especially brokerage companies establish management processes that contain a set of criteria for the organization and treatment of information collected in newspapers, news agencies and the companies that trade in stocks. Thus, it is essential to establish rigor in relation to recovery mechanisms of such information, which requires more than technology, because actions are necessary that will propitiate the informational content are made available with consistency, clarity and trustworthiness, so as that users can retrieve them in a timely manner. Furthermore, those processes should provide the efficient use of the information retrieved by users, so that they can use them aiming to subsidize the decisions of sale or purchase shares. Considering that the information systems are responsible for the information dissemination in the framework of capital market, it is necessary to present requisites that contemplate the set organization, treatment, retrieval and use of information. That way, we sought to evidence in this paper these issues, utilizing as a premise the elements proposed by Guimarães (2003) from the perspective of the information environment of a values brokerage companies reflecting through the model used, how these companies realize their work considering the dimensions of the documentary analysis, informational treatment, and the instruments for retrieval and use of information.

No mercado de capitais as informações são utilizadas como subsídios para a tomada de decisão de investidores, entre as principais destacam-se as de cunho econômico, político, contábil e as referente aos resultados financeiros das empresas que possuem ações negociadas em Bolsa de Valores. Nessa perspectiva, é fundamental que os agentes envolvidos – principalmente as sociedades corretoras –, estabeleçam processos de gestão que contenham um conjunto de critérios para a organização e o tratamento das informações coletadas em jornais, agências de notícias e nas próprias empresas que negociam ações. Assim, é fundamental estabelecer rigor no que tange aos mecanismos de recuperação dessas informações, o que requer mais do que tecnologia, porquanto são necessárias ações que irão propiciar que os conteúdos informacionais sejam disponibilizados com consistência, clareza e fidedignidade, de forma que os usuários possam recuperá-los em tempo hábil. Além disso, esses processos devem proporcionar o uso eficiente das informações recuperadas pelos usuários, de modo que possam utilizá-las visando subsidiar as decisões de compra ou venda de ações. Considerando que os sistemas de informação são responsáveis pela disseminação de informações no âmbito do mercado de capitais, é preciso apresentar quesitos que contemplem o conjunto organização, tratamento, recuperação e uso de informações. Dessa forma, buscou-se evidenciar neste trabalho tais quesitos, utilizando-se como premissa os elementos propostos por Guimarães (2003) sob a perspectiva do ambiente informacional de uma sociedade corretora de valores, refletindo através do modelo utilizado, o quanto essas empresas realizam seus trabalhos considerando as dimensões da análise documentária, do tratamento informacional e dos instrumentos para recuperação e uso da informação.
Information management process: Treatment, recovery and use of information in the capital market
Keywords: Gestão da Informação; Mercado de Capitais; Sistemas de Informação; Tratamento da Informação; Recuperação da Informação; Uso da Informação